SMILE and Wavefront-Guided LASIK Out-Compete Other Refractive Surgeries in Ameliorating the Induction of High-Order Aberrations in Anterior Corneal Surface - Min-jie Ye; Cai-yuan Liu; Rong-feng Liao; Zheng-yu Gu; Bing-ying Zhao; Yi Liao (Journal of Ophthalmology)
Purpose. To compare the change of anterior corneal higher-order aberrations (HOAs) after laser in situ keratomileusis (LASIK), wavefront-guided LASIK with iris registration (WF-LASIK), femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK), and small incision lenticule extraction (SMILE). Methods. In a prospective study, 82 eyes underwent LASIK, 119 eyes underwent WF-LASIK, 88 eyes underwent FS-LASIK, and 170 eyes underwent SMILE surgery. HOAs were measured with Pentacam device preoperatively and 6 months after surgery. The aberrations were described as Zernike polynomials, and analysis focused on total HOAs, spherical aberration (SA), horizontal coma, and vertical coma over 6 mm diameter central corneal zone. Results. Six months postoperatively, all procedures result in increase of anterior corneal total HOAs and SA. There were no significant differences in the induced HOAs between LASIK and FS-LASIK, while SMILE induced fewer total HOAs and SA compared with LASIK and FS-LASIK. Similarly, WF-LASIK also induced less total HOAs than LASIK and FS-LASIK, but only fewer SA than FS-LASIK (P<0.05). No significant difference could be detected in the induced total HOAs and SA between SMILE and WF-LASIK, whereas SMILE induced more horizontal coma and vertical coma compared with WF-LASIK (P<0.05). Conclusion. FS-LASIK and LASIK induced comparable anterior corneal HOAs. Compared to LASIK and FS-LASIK, both SMILE and WF-LASIK showed advantages in inducing less total HOAs. In addition, SMILE also possesses better ability to reduce the induction of SA in comparison with LASIK and FS-LASIK. However, SMILE induced more horizontal coma and vertical coma compared with WF-LASIK, indicating that the centration of SMILE procedure is probably less precise than WF-LASIK.